Fenomena Sosial Olahraga Lari: Studi Kasus Pada Gelora Kadrie Oening Kota Samarinda - Hardiansyah M, Muhammad Arfan (Institut Agama Islam Sunan Giri Ponorogo, 2025)
This study aims to analyze the social phenomenon of running in Gelora Kadrie Oening, Samarinda City, with a focus on the factors that influence community participation in this activity, as well as its impact on social interaction and mental health. Running, which was originally an individual activity, has now developed into an organized activity in running communities. Through a qualitative case study approach, this research collected data through in-depth interviews, participatory observation, and documentation. The results show that there is a significant increase in community participation in running sports at Gelora Kadrie Oening, which is driven by awareness of a healthy lifestyle. This phenomenon also forms running communities that strengthen social relationships between individuals. In addition to physical benefits such as improved cardiovascular fitness, running also has a positive impact on mental health, helping to reduce stress and improve mood. The study also found that running has a positive impact on the local economy, with increased sales by local merchants and the involvement of local sponsors in running events. Overall, the social phenomenon of running in Gelora Kadrie Oening reflects the changing lifestyle of people who are more aware of the importance of health and social relationships and contributes to the social dynamics in Samarinda City.